2012
DOI: 10.1080/13573322.2011.608937
|View full text |Cite
|
Sign up to set email alerts
|

Sports coaching in risk society: No touch! No trust!

Abstract: This paper is informed by a UK based Economic and Social Research Council funded research project which developed and deployed a case-study approach to issues of touch between children and professionals in schools and childcare. Outcomes from these settings are referred to, but the focus here is shifted to touch in sports coaching and its distinctive contextual and institutional characteristics. We consider the broader context of no touch coaching practice, including relevant theoretical accounts, review polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…Estos son higiene (PEDRAZA, 2011), epidemiología (BAGRICHEVSKY;ESTEVÃO, 2012;KELLEY;SMITH, 2004;RAIL;HOLMES;MURRAY, 2010), obesidad (MORALES; FILOMENA; JIM; NORTE; ANDALUZ, 2013;RAIL et al, 2010;RAIL;, VALBUENA et al, 2015WACHS;CHASE, 2013;WARIN, 2010), deporte (MALCOLM, 2014;PIGGIN;BAIRNER, 2014;PIPER;GARRATT, 2012), salud (ARBOLEDA, 2013;MARTÍNEZ, 2011;MORALES et al, 2013;PALACIOS;RICO, 2011;PANIER, 2009) y mercado (ARREGUIN;SANDOVAL, 2014;SOSSA, 2011). Estas investigaciones permitieron contextualizar y abordar la temática de una manera profunda.…”
Section: Estilos De Vida Saludable: ¡No Al Sedentarismo!unclassified
“…Estos son higiene (PEDRAZA, 2011), epidemiología (BAGRICHEVSKY;ESTEVÃO, 2012;KELLEY;SMITH, 2004;RAIL;HOLMES;MURRAY, 2010), obesidad (MORALES; FILOMENA; JIM; NORTE; ANDALUZ, 2013;RAIL et al, 2010;RAIL;, VALBUENA et al, 2015WACHS;CHASE, 2013;WARIN, 2010), deporte (MALCOLM, 2014;PIGGIN;BAIRNER, 2014;PIPER;GARRATT, 2012), salud (ARBOLEDA, 2013;MARTÍNEZ, 2011;MORALES et al, 2013;PALACIOS;RICO, 2011;PANIER, 2009) y mercado (ARREGUIN;SANDOVAL, 2014;SOSSA, 2011). Estas investigaciones permitieron contextualizar y abordar la temática de una manera profunda.…”
Section: Estilos De Vida Saludable: ¡No Al Sedentarismo!unclassified
“…Here, one's own feelings are denied as they are not considered organizationally or contextually appropriate (Potrac & Marshall, 2011). This was highlighted in a recent paper by Piper, Taylor and Garratt (2012) who argued that irrational defensiveness stemming from a fear of touch has tended to reduce much coaching input to emotionally anorexic instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this research, it has been suggested that coach-athlete sexual relationships can harm athletes' wellbeing, jeopardise athletic careers and performance ability, disrupt team dynamics, debilitate gender equality in sport, and also that an acceptance of such sexual relationships increases the risk of sexual exploitation (Brake, 2012;Kirby et al, 2000;Reaves, 2001;Toftegaard Nielsen, 2001;Volkwein et al, 1997). Meanwhile, additional literature suggest that mistrust of coaches motives related to fear of sexual abuse and harmful physical touch generate negative outcomes for coach-athlete interaction and more widely for sport policy and practice (Garratt et al, 2012, Lang, 2010Piper et al, 2012a;2012b). There is, however, no comprehensive research within the sociology of sport into coach-athlete sexual relationships outside the sexual abuse context.…”
Section: Introductionmentioning
confidence: 99%
“…This policy development may be located in a macro risk society context, where danger, mistrust and anxiety together with a growing awareness of sexual abuse and related moral panic necessitate protection (of young athletes) and control (of coaching practice) through extended surveillance, regulation and prohibition. For examples regarding physical touch and sexuality, see Garratt et al (2012), Lang (2010), Piper et al (2012a2012b); cf. Beck (1992) and Foucault (1977Foucault ( , 1978.…”
Section: A Deterministic Perspectivementioning
confidence: 99%